Evaluation of ProPath for control of liver abscesses, pulmonary lesions, and heat stress of feedlot beef cattle managed under a natural feeding protocol - Nelson, William Tyler, author; Wagner, John J., advisor; Archibeque, Shawn L., advisor; Koontz, Stephen R., committee member (Colorado State University. Libraries, 2020)
Thirty-two pens housing from 249 – 282 beef cattle each were used to evaluate the efficacy of a novel trace mineral source for control of liver abscesses, heat stress, and lung lesions in a feedlot setting. Arrival date and sex were used as blocking factors for a randomized complete block experiment design, with a total of 11 blocks of steers and five blocks of heifers. Trace minerals of interest were Co, Cu, I, Mn, Se, and Zn. The two treatments that were used were: 1) Control (n = 16 pens), with inorganic sources for all trace minerals of interest; and 2) Test (n = 16 pens), with ProPath (Zinpro Corporation, Eden Prairie, MN, USA) used to provide additional AA complexes of Zn and Mn, complexed Co, and ruminally-protected folic acid to basal control diet. All cattle within both treatments were fed to meet JBS "Aspen Ridge" beef labeling requirements. Cattle were not administered any ionophores, antimicrobials, β-andrenergic agonists, or growth-promoting implants. Cattle identified as sick and pulled from pens for administration of antimicrobials were removed from the study. Cattle were fed for approximately 180d at a commercial feedlot in Eastern Colorado. Liver abscesses were scored using the Elanco Liver Check System (Elanco, Greenfield, IN, USA). Lungs of harvested cattle were evaluated for presence of lesions tags using the system described by Tennant et al (2014). To evaluate heat stress, cattle were observed twice monthly from June – September. Three observations per observation day were made at these times: 1) 0700 – 1000; 2) 1015 – 1315; 3) 1430 – 1700 (all times ± 30 min). Hide temperatures were observed caudal to left glenohumeral joints of 10 black-hided and, when available, 10 non-black-hided animals per pen. Within each pen, surface temperatures were observed at 3 locations on the cement bunk apron and 7 locations on the dirt surface. Temperatures were observed using a Fluke VT04 visual infrared thermometer (Fluke Corporation, Everett, WA, USA). Performance data were collected and evaluated on all cattle. Hide temperatures were greater on black-hided cattle than non-black-hided cattle (P < 0.0001) and on steers than heifers (P < 0.0001). Hide temperatures on Test cattle were greater (P = 0.0008) than temperatures on Control cattle, but this effect was small (0.251o C) and inconsistent across observation days (treatment within date interaction: P < 0.0001). Pen-surface temperatures were greater in Time 2 than Time 1 (P < 0.0001), but not different between Time 2 and Time 3 (P = 0.37). Hide temperatures on all cattle were correlated with pen-surface temperature (R2 = 0.43). There were no differences between treatments for cattle observed open-mouth breathing (OMB, P = 0.22). Percentages of cattle observed OMB was different across all time points (P < 0.01). No differences were observed between sexes in Time A (P = 0.50) or Time B (P = 0.36), but percentages of heifers observed OMB were greater than percentages of steers observed OMB in Time C (P = 0.01; time point-by-sex interaction P < 0.01). There was also a significant time point-by-date interaction (P < 0.01). Based on these data, infrared hide temperature observed caudal to the glenohumeral joint is not likely to be a useful measurement of heat stress. ProPath did not lessen observed incidence of open-mouth breathing compared to inorganic sources of trace minerals in these cattle fed under a natural-feeding protocol. No treatment differences were observed for percent of livers containing any (P = 0.62), A+ (P = 0.14), A (P = 0.88), A- abscesses (P = 0.63). No significant differences were observed for sex for all liver abscesses (P = 0.32), A+ liver abscesses (P = 0.82), A liver abscesses (P = 0.72), or A- liver abscesses (P = 0.18). No treatment differences were observed for percent of cattle with mild (P = 0.64), moderate (P = 0.86), or severe (P = 0.30) pulmonary lesions. For percentage of cattle observed with any lung lesions, no differences were found between treatments (P = 0.51) or between sexes (P = 0.39). A sex-by-treatment interaction was observed for cattle with severe lung lesions (P < 0.01). Control animals achieved higher ADG than Test cattle on both a deads-and fallouts-in (P = 0.01) and deads-and fallouts-out (P = 0.03) basis. Control cattle achieved higher G:F than Test cattle when analyzed on a deads-and fallouts-in basis (P = 0.02), but not on a deads-and fallouts-out basis (P = 0.92). Control cattle achieved greater HCW (P = 0.03), FT (P = 0.04), and marbling score (P = 0.05). No other differences were found in carcass metrics between treatments (P > 0.05).